2017
DOI: 10.5935/abc.20170035
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Muscle Free Strain in Patients with Severe Degenerative and Functional Mitral Regurgitation

Abstract: FundamentoThe role of papillary muscle function in severe mitral regurgitation with preserved and reduced left ventricular ejection fraction and the method of choice to evaluate PM have still been the subjects of controversy.ObjectivesTo evaluate and compare papillary muscle function in and between patients with severe degenerative and functional mitral regurgitation by using the free strain method.Methods64 patients with severe mitral regurgitation - 39 patients with degenerative mitral regurgitation (DMR gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…4. These computed temporal myofiber stretch evolutions are in line with clinical observations for non-diseased human hearts, measured with both ultrasound and magnetic resonance imaging techniques [54][55][56][57]. Naturally, the corresponding pressure-volume loops and cardiac output remain constant.…”
Section: Mechanical Drug Effectssupporting
confidence: 81%
“…4. These computed temporal myofiber stretch evolutions are in line with clinical observations for non-diseased human hearts, measured with both ultrasound and magnetic resonance imaging techniques [54][55][56][57]. Naturally, the corresponding pressure-volume loops and cardiac output remain constant.…”
Section: Mechanical Drug Effectssupporting
confidence: 81%
“…По данным исследования, деформация инфарцированных сегментов являлась предиктором ИМР при нижнезаднем ИМ, а диссинхрония ПМ -предиктором ИМР при ИМ обеих локализаций. Работы, изучающие деформацию ПМ и их диссинхронию, малочисленны [9,10], а исследования в раннем периоде ИМ отсутствуют. По нашим данным диссинхрония ПМ >30 мс прогнозирует ИМР.…”
Section: Discussionunclassified
“…In a CMR study, Han et al described a higher excursion of the PMpm tip towards the mitral annular plane during systole in MVP patients compared with healthy volunteers; yet, did not compare it with the PMal (29). A more recent echocardiography study (30) found signi cantly lower longitudinal strain (i.e. less shortening) of the PMpm in MVP patients compared with controls (-30.5% vs. -43%), with no differences regarding the PMal, suggesting more pronounced mechanical stress of the posteromedial than the anterolateral PM.…”
Section: Detection Of Myocardial Brosismentioning
confidence: 99%